Study on gross streambank sediment erosion from the Godavari Khola, southeast Kathmandu Valley, Central Nepal (Journal of Nepal Geological Society, 2018)
The fifth order Godavari Khola is flowing from the South to the North direction and is one of the major tributaries from the southern part of the Kathmandu Valley. As the urbanization is growing in the Kathmandu Valley the banks of the streams are being targeted for the housing and roads, therefore it is important to know the characteristic of the river behavior, nature of erosion and sediment production along its banks. This study accesses the stream bank erosion characteristics and sediment production by erosion along the Godavari Khola. It was conducted by surveying and accessing hydraulic parameters, Bank Erosion and Lateral Instability status, streambank recession rates and gross sediment erosion from the bank.The Godavari Khola has high bank erodibility and lateral instability as the hazard level of Bank Erosion and Lateral Instability (BELI) and width/depth ratio are quite high. Since the slope and the bankfull depth exceed the critical slope and critical depth values, respectively, the Godavari Khola is competent enough to mobilize its sediments. The apparent recession rate of the banks of the Godavari Khola is 0.66 m per year yielding 85 m3 volume of the displaced material which weighs 141 tonnes. The estimated bank erosion rate is in between 0.02 to 0.235 m/y and the gross erosion is estimated to be 320 tonnes per year. Similar to the other river of the Kathmandu Valley, the Godavari Khola is very disturbed by the anthropogenic activities. Riparian vegetation clearing and bad agricultural practice is one of the major causes for the high bank erosion and instability of the Godavari Khola.